2005
DOI: 10.1074/jbc.m414676200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Endosomal Cholesteryl Ester Metabolism by Membrane Cholesterol

Abstract: Cells acquire cholesterol in part by endocytosis of cholesteryl ester containing lipoproteins. In endosomes and lysosomes cholesteryl ester is hydrolyzed by acidic cholesteryl ester hydrolase producing cholesterol and fatty acids. Under certain pathological conditions, however, such as in atherosclerosis, excessive levels of cholesteryl ester accumulate in lysosomes for reasons that are poorly understood. Here, we have studied endosomal and lysosomal cholesteryl ester metabolism in cultured mouse macrophages a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
(33 reference statements)
2
10
1
Order By: Relevance
“…It is conceivable that once cholesterol displaced from A2E-containing membranes reaches a critical concentration, it is excluded from the pool destined for nonvesicular transport to the limiting membrane and thus gets trapped within the LE/Ly. Increased LE/Ly cholesterol levels result in an indirect inhibition of RPE acid lipase, in agreement with previous studies showing that late endosomal cholesterol efflux is necessary for acid lipase activity (19). The subsequent accumulation of CE along with free cholesterol generates a feed-forward cycle of further cholesterol accumulation, inhibition of acid lipase, and increased CE in the cell.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is conceivable that once cholesterol displaced from A2E-containing membranes reaches a critical concentration, it is excluded from the pool destined for nonvesicular transport to the limiting membrane and thus gets trapped within the LE/Ly. Increased LE/Ly cholesterol levels result in an indirect inhibition of RPE acid lipase, in agreement with previous studies showing that late endosomal cholesterol efflux is necessary for acid lipase activity (19). The subsequent accumulation of CE along with free cholesterol generates a feed-forward cycle of further cholesterol accumulation, inhibition of acid lipase, and increased CE in the cell.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, CE accumulation in RPE cells is not because of a direct inhibition of acid lipase by A2E. It has been proposed that CE hydrolysis in LE/Ly is biphasic; initial hydrolysis occurs until endosomal membranes become saturated with free cholesterol and further hydrolysis depends on desorption of cholesterol onto other membranes/carriers (19). Indeed, we found that increasing the cholesterol content of TFMUO micelles caused a marked decrease in acid lipase activity (Fig.…”
Section: A2e Causes Endogenous Cholesterol Accumulation In Rpe Cellssupporting
confidence: 46%
“…While the reduction of free cholesterol was significant, the magnitude of change among treatment groups was relatively small indicating that free cholesterol in cell membranes is tightly regulated due to its essential role in cell metabolism. The trend of increasing liver triacylglycerol possibly indicates that secretion of VLDL is decreased (Wang et al, 2005), although this was not measured in the current study. Liver phospholipid is an indicator of cell mass and was not affect by dietary treatment.…”
Section: Discussioncontrasting
confidence: 39%
“…Nohturfft and coworkers (47) have shown that when cholesterol levels of endosomal/lysosomal membranes are high, as is the case in NPC1-deficient hepatocytes, cholesterol can be esterified in endosomes/lysosomes. We, therefore, performed the cholesterol esterification assay with [ 3 H]oleate in the presence and absence of an inhibitor of acylCoA:cholesterol acyltransferase (Sandoz 50-035) (48).…”
Section: Npc1mentioning
confidence: 99%